Molecular structure of promoter-bound yeast TFIID. Issue 1 (December 2018) - Kolesnikova, Olga; Ben-Shem, Adam; Luo, Jie; Ranish, Jeff; Schultz, Patrick; Papai, Gabor
Abstract Transcription preinitiation complex assembly on the promoters of protein encoding genes is nucleated in vivo by TFIID composed of the TATA-box Binding Protein (TBP) and 13 TBP-associate factors (Tafs) providing regulatory and chromatin binding functions. Here we present the cryo-electron microscopy structure of promoter-bound yeast TFIID at a resolution better than 5 Å, except for a flexible domain. We position the crystal structures of several subunits and, in combination with cross-linking studies, describe the quaternary organization of TFIID. The compact tri lobed architecture is stabilized by a topologically closed Taf5-Taf6 tetramer. We confirm the unique subunit stoichiometry prevailing in TFIID and uncover a hexameric arrangement of Tafs containing a histone fold domain in the Twin lobe. Transcription preinitiation complex assembly begins with the recognition of the gene promoter by the TATA-box Binding Protein-containing TFIID complex. Here the authors present a Cryo-EM structure of promoter-bound yeast TFIID complex, providing a detailed view of its subunit organization and promoter DNA contacts.